Economic-Burden Trajectories in Commercially Insured US Infants With Respiratory Syncytial Virus Infection. (15th April 2019) - Chirikov, Viktor V; Simões, Eric A F; Kuznik, Andreas; Kwon, Youngmin; Botteman, Marc
Abstract: Background: This study evaluates the long-term respiratory syncytial virus (RSV) burden among preterm and full-term infants in the United States. Methods: Infants with birth hospitalization claims and ≥24 months of continuous enrollment were retrospectively identified in the Truven MarketScan Commercial Claims and Encounters database for the period 1 January 2004–30 September 2015. Infants with RSV infection in the first year of life (n = 38 473) were matched to controls (n = 76 825), and remaining imbalances in the number of individuals in each group were adjusted using propensity score methods. All-cause, respiratory-related, and asthma/wheezing-related 5-year average cumulative costs were measured. Results: Early premature (n = 213), premature (n = 397), late premature ( n = 4446), and full-term (n = 33 417) RSV-infected infants were matched to 424, 791, 8875, and 66 735 controls, respectively. After 2 years since RSV diagnosis, all-cause cumulative costs for RSV-infected infants as compared to those for controls increased by $22 081 (95% confidence interval [CI], −$5800-$42 543) for early premature infants, by $14 034 (95% CI, $5095– $22 973) for premature infants, by $10 164 (95% CI, $8835–$11 493) for late premature infants, and by $5404 (95% CI, $5110–$5698) for full-term infants. The 5-year RSV burden increased to $39 490 (95% CI, $18 217–$60 764), $23 160 (95% CI, $13 002–$33 317), $13 755 (95% CI, $12 097–$15 414), and $6631 (95% CI, $6060–$7202), respectively. The RSV burden was higher when stratified by inpatient and outpatient setting and respiratory-related and asthma/wheezing-related costs. Conclusions: The RSV burden extends across cost domains and prematurity, with the greatest burden incurred by the second year of follow-up. Findings are useful in determining the cost-effectiveness of RSV therapies in development. Abstract : This study bridges the critical knowledge gap regarding the long-term cost burden of respiratory syncytial virus in US infants, stratified by prematurity status and cost type, over 5 years of follow-up. These findings are useful in assessing the value of current and future RSV regimens.